Evaluation of Interleukin-23 and Creatine Kinase –MB (CK-MB) Levels in Acute Coronary Syndrome Patients with COVID-19 in Baghdad City - Zahraa kareem Yaseen; Farhan Abood Risan; Suhad Hassan Aubaid (Journal of Techniques)
Acute coronary syndrome (ACS) is considered a common cardiovascular disease, in which there is a blood supply reduction to the myocardium, mostly due to atherosclerosis in the coronary arteries. the present study was designed to detect serum markers in Acute coronary syndrome patients infected with COVID-19 in Baghdad Governorate, by evaluating the level of Interleukin-23(IL-23) and level of creatine kinase isoenzyme (CK-MB). Methods: A total of one hundred fifty participants were enrolled in the current study divided into three groups 50 patients with ACS and 50 ACS with COVID-19 patients, while 50 participants as apparently healthy controls. age and sex-matched as healthy controls were involved in the present study. The serum IL-23 and CK-MB levels were measured using an ELISA technique.